PROTOTYPE OF COOKING OIL VISCOSITY MEASURING INSTRUMENT USING LASER BEAM AND LIGHT DEPENDENT RESISTOR (LDR) - Firmansyah, Dudi Adi (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2025)
Cooking oil, especially palm oil, is one of the highest commodities produced and consumed by Indonesia. Throughout 2022, Indonesian people consumed 20.9 million tons of palm cooking oil. With the recent emergence of cooking oil dispensers, a regulation, method, or tool is needed to measure the quality of cooking oil stored in cooking oil dispensers. One of the factors that determines the quality of cooking oil is thickness or viscosity. The viscosity or thickness of cooking oil is greatly influenced by the temperature of the palm oil. Therefore, a prototype tool for measuring cooking oil viscosity was created using a laser module and a Light Dependent Resistor (LDR) sensor. This tool is based on a falling ball viscometer, where time recording is assisted by an internal timekeeper on the Arduino Uno. The results of testing the measuring instrument prototype at temperatures of 29 °C to 45 °C showed that the accuracy was more than 95.82% and the precision average is 94.73%. This prototype displays the viscosity measurement results on the I2C 16x2 LCD in Pa.s units and has a push button to hold the measurement result value.